Reappraisal of legacy reflection seismic data using advanced processing techniques and seismic attributes - Westgate, Michael Clifford (My University, 2020)
Reflection seismic data, once processed and interpreted, are typically archived and sometimes even discarded. This may happen especially when the data are initially acquired with specific goals in mind (such as mineral exploration) and are deemed as no longer useful after those goals have been realized. It is tempting to regard used data as useless, however in this thesis, I show how legacy seismic data can sometimes hold more value than they are credited and that, by repurposing them, they can provide insight into further areas of study. This is done via three investigations. First, I reprocess a legacy seismic profile originally intended for gold exploration in the southwestern margin of the Archaean (3.7–2.6Ga) Kaapvaal Craton (South Africa) and repurpose it for iron-oxide prospection. By integrating borehole data and seismic attributes, I quantify the subsurface geometry of haematite-hosting metasediments of the 2.64 –2.43 Ga Griqualand West Supergroup to reveal some degree of folding that locates these metasediments (~ 500 m thick) at a mineable depth of 900 m. This profile, located near Sishen iron mine, thus enhances our understanding of the strato-structural architecture and ore resource evaluation within the area. Second, I show how reprocessing a legacy seismic profile also intended for gold exploration can provide insight into the tectonically rich setting of the western margin of the Kaapvaal Craton, where the 1.2 Ga Kheis Province, 145 Ma Morokweng impact crater, and the associated first-order scale structures contribute in constraining the complex tectonic history of the region. Integrating the profile with borehole data suggests a significantly different interpretation of the supracrustals and their interaction with first-order scale faults to already-published interpretations. Furthermore, the reprocessed data exhibit strikingly improved imaging of the overlying Phanerozoic cover, revealing the 250 Ma Dwyka and 1.2 –1 Ma Kalahari Group sediments to show significant disruptions as a result of neotectonic activity. Third, I demonstrate how application of novel complex seismic attributes to legacy seismic cubes from both the onshore hard rock Witwatersrand Basin and the offshore Bredasdorp Basin can better improve the detection of thin (~ 2 m thick) gold-bearing horizons and hydrocarbon reservoirs, respectively. Before detailing these investigations, I lay the theoretical foundation thereof by providing sufficient geological background of each setting, a comprehensive review of the seismic processing sequence as applied to the two legacy profiles, a motivation for the value of legacy data as well as the challenges of its reappraisal, and an expository description of the composite seismic attributes used in my investigations
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, University of the Witwatersrand, 2020